Paper and fire eaudiobook - Caine, Rachel (The Great Library, 2016)
In Ink and Bone, New York Times bestselling author Rachel Caine introduced a world where knowledge is power, and power corrupts absolutely. Now, she continues the story of those who dare to defy the Great Library-and rewrite history. With an iron fist, The Great Library controls the knowledge of the world, ruthlessly stamping out all rebellion, forbidding the personal ownership of books in the name of the greater good. Jess Brightwell has survived his introduction to the sinister, seductive world of the Library, but serving in its army is nothing like he envisioned. His life and the lives of those he cares for have been altered forever. His best friend is lost, and Morgan, the girl he loves, is locked away in the Iron Tower and doomed to a life apart. Embarking on a mission to save one of their own, Jess and his band of allies make one wrong move and suddenly find themselves hunted by the Library's deadly automata and forced to flee Alexandria, all the way to London. But Jess's home isn't safe anymore. The Welsh army is coming, London is burning, and soon, Jess must choose between his friends, his family, or the Library willing to sacrifice anything and anyone in the search for ultimate control.